1997
DOI: 10.1002/(sici)1099-1379(199711)18:6<685::aid-job817>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of burnout among managers and professionals: a comparison of models

Abstract: SummaryUsing structural equation modeling, this paper compares the intertemporal sequences of the burnout components proposed by Maslach (1982) and Golembiewski (1989) using responses from 354 human resource professionals. The relationship between the burnout components and several critical variables that are theoretically linked to the phenomenon are also investigated. Studying human resource professionals allows us to examine the generalizability of burnout. This group of employees provides a range of servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(74 citation statements)
references
References 41 publications
5
65
0
4
Order By: Relevance
“…Consistent with Leiter's (1993) process model of burnout, feelings of exhaustion were positively related to disengagement. The burnout literature seems to systematically find evidence for this relationship (e.g., Cordes et al, 1997) and, consequently, this relationship should be added to the JD-R model. Apparently, employees attempt to gain emotional distance from their job as a way of coping with their work-related feelings of exhaustion.…”
Section: Other Relationships In the Jd-r Modelmentioning
confidence: 58%
See 1 more Smart Citation
“…Consistent with Leiter's (1993) process model of burnout, feelings of exhaustion were positively related to disengagement. The burnout literature seems to systematically find evidence for this relationship (e.g., Cordes et al, 1997) and, consequently, this relationship should be added to the JD-R model. Apparently, employees attempt to gain emotional distance from their job as a way of coping with their work-related feelings of exhaustion.…”
Section: Other Relationships In the Jd-r Modelmentioning
confidence: 58%
“…escape/emotion-focused coping; Latack & Havlovic, 1992). This model has been supported by several studies (e.g., Bakker, Schaufeli, Sixma, Bosveld, & Van Dierendonck, 2000;Cordes, Dougherty, & Blum, 1997). Thus, we assume that exhaustion fostered by job demands may evoke psychological withdrawal (cf.…”
Section: Interactions Between Job Demands and Resourcesmentioning
confidence: 99%
“…Support has been shown for test-retest reliability ranging from .60 to .82 (Bamett, Brennan, & Gareis, 1999;Byrne, 1994;Cordes, Dougherty, & Blum, 1997;Richardsen, & Martinussen, 2004; and there is evidence of convergent and discriminant validity (Cordes, Dougherty, & Blum, 1997;Demerouti, Bakker, Vardakou, & Kantas, 2003). Research also has found evidence for predictive validity of the MBI .…”
Section: Burnout the Maslach Burnout Inventorymentioning
confidence: 99%
“…Individuals at work cannot bear the burden of emotional exhaustion work is too monotonous, from which no sense of accomplishment, or lack of autonomy in the work, will make individuals unable to work in the self, and the formation of frustration, the final emotional retreat and physiological abnormalities and other phenomena and individuals face different contradictory role expectations, cannot be adjusted, to cope with, will also make emotional resources exhausted (Cordes & Dougherty, 1997) [21].…”
Section: University Faculties' Job Stress Job Burnout and Organizmentioning
confidence: 98%